Research on Differential Metabolites in Distinction of Rice (Oryza sativa L.) Origin Based on GC-MS - Yuchao Feng; TianXin Fu; Liyuan Zhang; Changyuan Wang; Dongjie Zhang (Journal of Chemistry)
The analytical method for the metabolomics of the 60 rice seeds from two main rice origins in Heilongjiang Province was developed based on gas chromatography coupled with mass spectrum. The specific differential metabolites between two rice origins were identified, and the distinguish of the two main origins was illustrated by using the R software platform with XCMS software package for gas chromatography coupled with mass spectrum data processing, combined with multivariate statistical analysis software. The result indicated that the 173 peaks were detected, and 54 of which were structurally identified, covering amino acids, aliphatic acid, sugar, polyols, and so on. By comparing the data of Wuchang and Jiansanjiang origins, it was found that there were 9 special metabolites in Wuchang origin and 8 special metabolites in Jiansanjiang origin. The 10 differential metabolites with significant changes (P<0.05, VIP ≥ 1) were filtrated. It is indicated that the differential metabolites of rice carry information of their origin and there are the differences in the metabolites of rice in two main origins. The proposed method is expected to be useful for the metabolomic researches of rice.